Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/froh.2021.628026
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behavior and Surface Quality of Dental Bioactive Ions-Releasing Resins Under Simulated Chewing Conditions

Abstract: Bioactive materials can reduce caries lesions on the marginal sealed teeth by providing the release of ions, such as calcium, phosphate, fluoride, zinc, magnesium, and strontium. The presence of such ions affects the dissolution balance of hydroxyapatite, nucleation, and epitaxial growth of its crystals. Previous studies mostly focused on the ion-releasing behavior of bioactive materials. Little is known about their wear behavior sealed tooth under mastication. This study aimed to evaluate the wear behavior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
2
1
0
1
Order By: Relevance
“…However, water storage did not significantly affect the K IC , therefore this was the most stable material studied. The fact that the Fuji II LC is quite resistant to water-induced deterioration has been reported in previous studies about RMGIC; this property has been ascribed to the formation of a more robust polysalt matrix after water storage [32,33].…”
Section: Discussionsupporting
confidence: 57%
“…However, water storage did not significantly affect the K IC , therefore this was the most stable material studied. The fact that the Fuji II LC is quite resistant to water-induced deterioration has been reported in previous studies about RMGIC; this property has been ascribed to the formation of a more robust polysalt matrix after water storage [32,33].…”
Section: Discussionsupporting
confidence: 57%
“…Studies have shown that microhardness values of a composite can be affected by several factors such as organic and inorganic composition, filler content and the distribution on the surface, and degree of C=C conversion in methacrylate groups and cross-linking density. 45,46 In this study, a linear correlation (R 2 = 0.86) can be observed between the filler content (wt.%) and the microhardness (Fig. 6).…”
Section: Discussionsupporting
confidence: 66%
“…This would have facilitated their uptake by the sealant to recharge it with ions. This in turn would have reflected on incorporating minerals onto the enamel surface [ 30 ]. It was markedly noticed that percentage decrease of P ions from demineralization to remineralization was significantly lower with fluoride sealant than with bioactive sealant.…”
Section: Discussionmentioning
confidence: 99%